The Characterization of Synthetic Zeolite for Hydrocracking of Waste Cooking Oil into Fuel - Siti Salamah; Agus Aktawan; Ilham Mufandi (Dept. of Chemical Engineering, Diponegoro University, 2020)
Zeolite A was used as hydrocracking catalyst to convert cooking oil into potential renewable fuels. The experiment was performed by characterize the diffraction, and pore properties the synthetic zeolite and it was confirmed the synthetic zeolite was zeolite A. The hydrocracking process of waste cooking oil was carried out in semi-fixed batch reactor system at 450° C for 2 hours, under the hydrogen flow of 20 ml/minute. The diffractogram and Si/Al ratio, 1.6, were matched to zeolite A properties, with the surface area, pore diameter, and pore volume were, 1.163 m2/g, 3.93 nm, and 0.001 cc/g, respectively. Liquid product from hydrocracking process of cooking oil consisted of 28.99% alkane and alkene 26.59% that are potential as renewable fuels.Keywords: waste cooking oil; zeolite A; hydrocracking